Social capital is subordinate to natural capital in buffering rural livelihoods from negative shocks: Insights from rural South Africa. (January 2019) - Mbiba, Monicah; Collinson, Mark; Hunter, Lori; Twine, Wayne
Abstract: Rural livelihoods in developing countries are disproportionately vulnerable to multiple shocks and stresses that exacerbate vulnerability, which can result in increased dependence on natural resources. Several studies have been conducted on the safety net role of natural resources, which lower the impact of negative shocks on rural livelihoods. However, the role of social capital as a safety net that can potentially lower natural resource use when households experience negative shocks has been less studied. We examined the role of natural resources and social capital as buffers against negative shocks to reduce vulnerability in rural livelihoods. Using five years of panel data from a rural population in South Africa, multilevel models were constructed to quantify the influence of shocks, social capital and household socio-demographic characterization on three dimensions of natural resource use, namely the number of types of natural resources used, the frequency of natural resource use, and the quantities of natural resources used. Results show that household experience of negative shocks was consistently associated with a significant increase in all dimensions of natural resource use. However, and unexpectedly, social capital did not significantly reduce natural resource use when households experienced shocks. This in no way discounts the role social capital plays in cushioning households post experience of shocks, but rather indicates that reliance on social and natural capital could be complementary rather than substitutable coping strategies post experience of shocks. Efforts to secure rural livelihoods and achieve sustainability should thus focus on building household physical capital to reduce dependency on natural resources in rural households. Highlights: Negative shocks precipitate greater use of natural resources. Safety net role of social capital is not sufficient to reduce natural resource use. Social and natural capitals are complementary coping strategies post experience of shocks. Building household wealth is key to reducing dependency on natural resources use.